Batas Maksimum Suku Bunga Financial Technology Lending Terhadap Nasabah Pinjaman Online - Suryono, Darla Pratista Widyadhana; Fitriana, Zuhda Mila (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2025)
Online loans, also referred to as pinjol, are well recognized among the Indonesian population. Online lending is a business activity that involves lending money through digital platforms. It is supervised by the Financial Services Authority (OJK). However, not all players in the online lending industry comply with regulations, especially when it comes to determining interest rates. This is due to the lack of stringent and comprehensive regulations governing the determination of interest rates by the OJK, which allows several economic actors to use these rules. Currently, there are still numerous online loan applications that violate existing standards by setting interest rates that are not in compliance. These applications remain easily accessible to the public, which can have detrimental effects on individuals' lives, particularly among younger generations. In order to address and mitigate the issues that develop, it is imperative for the government to play a crucial role in making concerted efforts to resolve these problems, thereby ensuring that clients utilizing this online lending platform consistently have a sense of security and comfort. The findings of this study indicate that there are several online loan applications that remain valid but fail to adhere to requirements when it comes to disclosing interest rates to customers. This non-compliance has adverse effects for customers, both in terms of tangible and intangible consequences. Hence, in this particular scenario, the involvement of the OJK is indispensable in overseeing the participants of the internet lending industry and ensuring the safeguarding of customers utilizing these services.